Effects of Rhubarb combined with ulinastatin on T-cell subsets in sepsis rats - Tian, Huiyu (Int J Clin Exp Med, 2015)
Objective: The pathogenesis of sepsis, a systemic inflammatory response syndrome, is very complicated and not well understood. However, the importance of lymphocyte percentage and ratio is implicated. Rhubarb is a traditional Chinese medication and plays a role in protecting gastrointestinal mucous and controlling the SIRS damage. Ulinastatin is a protease inhibitor that prevents overproduction of inflammatory cytokines. Currently, despite numerous sepsis clinical researches, the study on the effects of combined drug therapy on sepsis is lacking. In this study, we studied Rhubarb and Ulinastatin combination treatment on T lymphocyte subsets in sepsis induced by the cecal ligation and perforation (CLP). Immunosuppression happened at the early stage of severe sepsis in the CLP rat models, as CD3(+), CD4(+), CD4(+)/CD8(+) began to decline, dropped rapidly after 24 h and continuously decreased at 36 h. CD8(+) T lymphocyte showed no significant change in all groups after CLP. The morality of CLP rats was increased with Rhubarb treatment in test dose (1.2 g/100 g). The immunosuppression state of CLP rats ameliorated with UTI treatment at early stage. The immunomodulatory properties were improved along with drug treatment, and immunities were obviously increased after 24 h, moreover, continuously increased at 36 h. The relief effect of immunosuppression after CLP showed much better in Rhubarb combined with UTI treatment than UTI monotherapy. In conclusion, the combination drug treatment facilitates the improvement of sepsis by modifying the lymphocyte percentage.